Atrial Fibrillation Is Associated With Increased Mortality in Patients Undergoing Transcatheter Aortic Valve Replacement: Insights From the Placement of Aortic Transcatheter Valve (PARTNER) Trial. (January 2016) - Biviano, Angelo B.; Nazif, Tamim; Dizon, Jose; Garan, Hasan; Fleitman, Jessica; Hassan, Dua; Kapadia, Samir; Babaliaros, Vasilis; Xu, Ke; Parvataneni, Rupa; Rodes-Cabau, Josep; Szeto, Wilson Y.; et al.
Abstract : Background—: This study sought to evaluate the impact of atrial fibrillation (AF) on clinical outcomes in patients undergoing transcatheter aortic valve replacement. Methods and Results—: Data were evaluated in 1879 patients with baseline and discharge ECGs who underwent transcatheter aortic valve replacement in the Placement of AoRTic TraNscathetER Valve (PARTNER) trial. A total of 1262 patients manifested sinus rhythm (SR) at baseline/SR at discharge, 113 SR baseline/AF discharge, and 470 AF baseline/AF discharge. Patients who converted from SR to AF by discharge had the highest rates of all-cause mortality at 30 days ( P <0.0001 across all groups; 14.2% SR/AF versus 2.6% SR/SR; adjusted hazard ratio [HR]=3.41; P =0.0002) and over 2-fold difference at 1 year ( P <0.0001 across all groups; 35.7% SR/AF versus 15.8% SR/SR; adjusted HR=2.14; P <0.0001). The presence of AF on baseline or discharge ECG was a predictor of 1-year mortality (adjusted HR=2.14 for SR/AF group and HR=1.88 for AF/AF groups; P <0.0001 for both groups versus SR/SR). For patients discharged in AF, those with lower ventricular response (ie, <90 bpm) experienced less 1-year all-cause mortality (HR=0.74; P =0.04). Conclusions—: After transcatheter aortic valve replacement, the presence of AF at discharge, and particularly, the conversion to AF by discharge and higher ventricular response are associated with increased mortality. These data underscore the deleterious impact of AF, as well as the need for targeted interventions to improve clinical outcomes, in patients undergoing transcatheter aortic valve replacement. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00530894.